Links between phenology and ecophysiology in a European beech forest - Urban J; Bednárová E; Plichta R; Gryc V; Vavrčík H; Hacura J; Fajstavr M; Kučera J (iForest - Biogeosciences and Forestry, 2015)
Over the course of a year, tree physiological processes are not only directly affected by environmental conditions, but also by the tree’s own phenological stages. At the same time, phenological stages should, to a certain degree, reflect tree physiology. However, we have rather poor knowledge of the details of the interplay between phenology and ecophysiology. The objective of this study was to develop a better understanding of the links between phenology and ecophysiology. We investigated the degree to which various physiological processes are synchronized both with each other and with phenology and what information related to phenology can be obtained from instrumental ecophysiological measurements. Phenological observations, along with measurements of transmittance of photosynthetically active radiation (PAR), stem volume changes, sap flow and xylogenesis were conducted in a 45-year old European beech (Fagus sylvatica) stand in the Czech Republic. Results indicated that ecophysiology was tightly related with the phenological stage of the tree. Early spring phenological stages were closely linked with the beginning of cambial activity and the onset of sap flow, i.e., the first leaves were produced simultaneously with the beginning of stem radial growth. The highest xylem growth rates occurred in June, simultaneously with the highest sap flow rates. Cambial activity ceased with the onset of summer leaf coloring at the end of July, at the same time as the permanent decrease in sap flow rate. The end of cell wall maturation was linked to the onset of autumn leaf coloring. We conclude that instrumental measurements of tree and stand ecophysiology provided additional information better specifying the onset of particular phenostages. In our case, twelve permanently located sensors used to measure PAR transmittance captured leaf area development with acceptable accuracy, thus limiting the need for frequent visits to the forest site in the spring and autumn. Moreover, data from dendrometers showed linkages to bud break and the onset of leaf coloring. Therefore, ecophysiological measurements increased the effectiveness and accuracy of phenological observations and provided additional information about tree development in particular external conditions.